The Effect of Project Based Learning (PjBL) Integrated by STEM on Students’ Generik Science Abilities - Qahfi, Bung Ashabul; Doyan, Aris; Makhrus, Muh. (Pascasarjana, Mataram University, 2024)
This research aims to determine the effect of the integrated STEM project-based learning (PjBL) model in static fluid material on the generic science abilities of students at SMAN 1 Donggo. The type of research is quasi-experimental research with a pretest and posttest design with non-equivalent control groups. The sample used was class XI where MIA 1 was the experimental class and class MIA 2 was the control class. The instrument used in collecting data is a test instrument in the form of multiple-choice questions. The data analysis technique used is the n-gain test. The research results show that the average n-gain value for critical thinking skills for both classes is an n-gain value of 53.43%, a minimum value of 11.67, and a maximum value of 85.11 for the experimental class. while the average n-gain value for the control class was 44.46%, the minimum value was 17.81 and the maximum value was 72.34. Based on these values, it is concluded that the STEM integrated project-based learning (PjBL) model has an effect on students' generic science abilities.